Peran Gaya Kepemimpinan, Budaya Organisasi dan Reward Terhadap Komitmen Kerja Karyawan - Lilik Kustiani; Diah Widiawati; Kurnia Isnuwardiati (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2021)
Employees who have a high commitment, have a desire to defend themselves as members of the organization. Therefore, to develop an organization, various aspects must be considered that can create work commitment. This study aims to examine: 1) the influence of leadership style on work commitment, 2) the influence of organizational culture on work commitment and 3) the effect of reward on work commitment. This research is a quantitative descriptive study using multiple regression analysis. The population in this study was all employees at KOPPAS "Citra Kartini" Senggreng Sumberpucung Malang Regency with a sample using saturated sampling technique, amounting to 39 employees. The results of data analysis in this study can be concluded: 1) leadership style has a significant positive effect on employee commitment, 2) organizational culture has a significant positive effect on employee commitment, 3) reward has a significant positive effect on employee commitment, and 4) reward is a variable which has a dominant effect on employee commitment